From abstract principles to specific urban order: Applying complexity theory for analyzing Arab-Palestinian towns in Israel. (February 2017) - Totry-Fakhoury, Maisa; Alfasi, Nurit
Abstract: This paper uses complexity theory to analyze the urban order and development of Arab Palestinian villages and towns in Israel. It follows the spontaneous emergence of abstract planning codes and principles, influenced by changing social, political and cultural dynamics. Based on a morphological analysis of 77 towns in northern and central Israel, and an in-depth investigation conducted in the city of Sakhnin, in the central Galilee, the paper reveals a repeated three-ring structure, corresponding to three socio-political periods. We offer a detailed examination of the links between social values and spatial conduct, thus enabling us to follow how slight changes in social and economic circumstances affect planning principles. In addition, the paper highlights the power of planning-without-a-plan as a method that facilitates shaping the quality of the built environment while allowing local adaptation and creativity. Finally, we discuss the problematic urban pattern created in the typical third ring, which is a top-to-bottom product of modern planning thought. Highlights: The paper uses complexity theory to analyze the urban order and development of Arab Palestinian villages and towns in Israel. The analysis follows the spontaneous emergence of abstract planning codes and principles, influenced by changing social, political and cultural dynamics. Based on a morphological analysis of 77 towns in northern and central Israel, and an in-depth investigation conducted in the city of Sakhnin, in the central Galilee, the paper reveals a repeated three-ring structure, corresponding to three socio-political periods. A detailed examination of the links between social values and spatial conduct shows how slight changes in social and economic circumstances affect planning principles and impact the built environment. The paper highlights the power of planning-without-a-plan as a method that shapes the quality of the built environment while allowing local adaptation and creativity.